Methotrexate Hepatotoxicity in Psoriatics: Report of 104 Patients from Nova Scotia, with Analysis of Risks from Obesity, Diabetes and Alcohol Consumption During Long Term Follow-Up. (1st October 1996) - Malatjalian, DA; Ross, JB; Williams, CN; Colwell, SJ; Eastwood, BJ
Abstract : BACKGROUND AND DESIGN: Methotrexate (MTX) hepatotoxicity in psoriatic patients is well recognized, but there are discrepancies in the reported incidence and associated risk factors. This retrospective study describes 104 Nova Scotian patients with psoriasis seen between 1979 and 1990. Patients received MTX over one to 11 years (mean 3.38), with baseline and annual follow-up liver biopsies. Clinical data were obtained by chart review. Statistical analysis evaluated the risks associated with obesity, diabetes, alcohol consumption and duration of therapy, with the histological grade of liver biopsies. RESULTS: Of the 104 patients, 35 were obese, 10 were diabetic and 37 occasionally consumed alcohol. At the end of the study, 21 patients had developed severe hepatic fibrosis (grade IIIB), and three developed liver cirrhosis (grade IV). Significant risk of severe hepatotoxicity is related to diabetes (P=0.02) but not to obesity (P=0.12) or alcohol consumption (P=0.12). All patients with cirrhosis took MTX for two years in standard doses of 20 to 25 mg/week. CONCLUSIONS: In this first Canadian study evaluating MTX hepatotoxicity in psoriatics, the incidence of severe hepatotoxicity is high: 23.1% (24 of 104 patients). This study shows that diabetic patients are particularly at increased risk of MTX hepatotoxicity. Occasional alcohol consumption is not associated with increased risk. Three patients who developed cirrhosis over two years of standard MTX therapy may represent a subset of psoriatics with increased hepatic susceptibility to MTX. Another three patients whose severe hepatic fibrosis had regressed upon discontinuation of MTX, but who developed accelerated recurrence of the severe hepatic fibrosis upon resumption of MTX therapy, also suggest the possibility of unusual sensitivity to the drug. These cases emphasize the need for continuing surveillance, with regular liver biopsies, of psoriatic patients on MTX.